Hikmah dan Nilai-nilai Pendidikan Adanya Ayat-ayat Muhkamat dan Mutasyabihat dalam Al-Qur’an - Diah Rusmala Dewi; Ghamal Sholeh Hutomo (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This study aims to analyze the wisdom and educational values of the verses of Muhkamat and Mutasyabihat in the Qur'an. The method used in this research is library research where the writer tries to find, compile and analyze various information through various related sources. The Qur'an has functions as a bayan (explanatory) and hudan (guidance) which contains an explicit verse or muhkam. Besides, it also has functions as the greatest miracle and literary book in human history which contains an implicit verse or mutasyabih that will never end to be studied and researched. Muhkamat and mutasyabihat verses are two complementary things in the Qur'an. There is an immeasurable wisdom and educational value for both. Therefore, in learning and understanding both is as well as learning the wisdom of decreasing the Qur'an itself.